2019
DOI: 10.9734/ijtdh/2019/v35i130115
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the Prostate Presenting as a Soft Tissue Metastasis: A Case Report and Review of Literature

Abstract: Metastasis is the most frequent cause of mortality in cancer patients and symptoms related to a secondary deposit are a common form of presentation in malignancies. Cancers of the prostate commonly present with metastasis to the vertebrae, and less commonly to the lungs and liver. Metastasis to soft tissue is extremely rare and a highly unlikely form of presentation. However, with rising cancer rates in the developing world, secondary tumors should be excluded when soft tissue masses are encountered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The presence of soft tissue metastases from a prostate adenocarcinoma is extremely rare, with only a handful of case reports being published in the literature. [4][5][6][7][8][9] The soft tissue metastasis may be the index presentation for the diagnosis of mCaP, [4][5][6][7] as was the case in our patient, or it may occur a few years after the initial diagnosis of mCaP. 8,9 Of the six reports identified in the literature, three authors reported cases with proven orbital soft tissue metastases.…”
Section: Discussionmentioning
confidence: 93%
“…The presence of soft tissue metastases from a prostate adenocarcinoma is extremely rare, with only a handful of case reports being published in the literature. [4][5][6][7][8][9] The soft tissue metastasis may be the index presentation for the diagnosis of mCaP, [4][5][6][7] as was the case in our patient, or it may occur a few years after the initial diagnosis of mCaP. 8,9 Of the six reports identified in the literature, three authors reported cases with proven orbital soft tissue metastases.…”
Section: Discussionmentioning
confidence: 93%